Placental Abruption: Temporal Trends, Risk Factors, and Associated Adverse Maternal Outcomes - Wright, Gillian L.; Friedman, Alexander; Ananth, Cande V.; Wen, Timothy (American Journal of Perinatology, 2025)
This study aimed to evaluate trends in placental abruption during delivery hospitalizations and associated risk factors and adverse outcomes.Delivery hospitalizations with and without placental abruption were identified using billing codes in the 2000 to 2020 National Inpatient Sample for this serial cross-sectional study. Temporal trends in abruption were analyzed with Joinpoint regression to determine the average annual percentage change (AAPC) in abruption. The association between hospital, demographic, and clinical factors and abruption was analyzed with adjusted logistic regression models with adjusted odds ratios (ORs) with 95% confidence interval (CI) as measures of association. Logistic regression models were then performed to assess the odds of adverse outcomes, including transfusion and severe maternal morbidity associated with abruption, accounting for demographic, hospital, and patient factors. Associations between changes in abruption and trends in the risk for adverse outcomes were then analyzed.Of 80.2 million deliveries from 2000 to 2020, 1.1 million had an abruption diagnosis. Placental abruption risk increased from 1.2% of deliveries in 2000 to 1.6% in 2020 (AAPC: 1.6%, 95% CI: 1.3%, 2.0%). Abruption was associated with multiple gestations, hypertensive diagnoses, diabetes, asthma, and Medicaid insurance. In adjusted analyses, abruption was associated with a range of adverse outcomes including transfusion (OR = 6.86, 95% CI: 6.70, 7.03), non-transfusion severe maternal morbidity (OR = 4.05, 95% CI: 3.93, 4.17), postpartum hemorrhage (OR = 1.76, 95% CI: 1.72, 1.80), disseminated intravascular coagulation (OR = 6.30, 95% CI: 6.00, 6.61), and critical care procedures (OR = 4.76, 95% CI: 4.26, 5.32). The increase in abruption accounted for 1.1% of the population change in transfusion risk over the study period.The risk for abruption increased over the study period and was associated with several adverse outcomes. Abruption accounted for a modest increase in population-level adverse outcomes. Given the increasing incidence, placental abruption will likely continue to be a significant source of adverse obstetric outcomes.
Keywords: placental abruption; severe maternal morbidity; maternal outcomes